(3GdGMJQGS Yf fGQ GdfHQGSs - (3ESMGb Hf Ydj (B((3Gh eMeO(B) (3GdYHOj Gdjefj,J (B1115 (3g` s ((3GSeGYjd Hf eMSf Hf Ydi GdMGL GdTGWHi s)
(3ChdgG (B:s
(3cJGH GdJhMjO GdJhMjO Cf dG JJhgeg , bGd GdeYJQV GYde Cf GdJhMjO eG jMVQ hLhH GdhLhO ajg JYGdi Ch jMVQ GdNGdbjI Ch jMVQ GdGdhgjI s
(3BNQgG (B:s
(3hbO CXgQ hCfge jNhWhf eG bO GVdhg ef Gdbhd ai UaGJ GdeYGfi hfMf YGdehf HCfge hEf cGfhG ai GbhGdge jXgQhf Cfge Je s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B296s
(3JHUQGJ GdCUd (B:s
Keywords: (3eJaQbGJs